Improving Civics Education Quality Through Two Stay Two Stray Technique: Classroom Action Research At Smk Negeri 2 Purbalingga 2010 - 2011 - K A M S O N , K A M S O N (2012)
In essence, the learning process subjects Citizenship Education can be performed with various models and techniques. Models and techniques of learning works to facilitate students learning the material presented by the teacher, so as to increase student competence that ultimately increase learning outcomes. The research objective of this class action is to enhance the learning process and improve learning outcomes of students at SMK Negeri 2 Purbalingga through Two techniques stay two stray. Formulation of the problem in this study is "How the quality of the learning process of Citizenship Education at SMK N 2 Purbalingga years 2010-2011. This research was conducted by research design class action through 3 cycles and ach cycle conducted 2 meetings. Each cycle consists of four measures, planning, implementation, observation and reflection. Source of research data include primary data and secondary data. Measure of the success of class actions is an increase in learning outcomes so completely100%. The data analyzed are the results of the evaluation data(test results of student learning) and non-test of observational data from the observer. The results showed that two stray stay Two techniques to improve student learning outcomes proved the value of the average pre-cycle 48, cycle 1 score of 64, seklus 2 score 3 score of 68 and 72 cycles. Also increase the activity of the learning process that teachers do. Based on the observation sheet that has been filled by the observers obtained results of teacher activity score of7.7 in cycle 1, cycle 2 score of 8.33 and at the end of cycle 3score of 9.16. Likewise, students in the learning activities also increased. Initial cycle of a student activity reached 68.9, a 72.8cycle 2 and cycle 3 to 77.6. For group activities increased from a score of 81 in cycle 1, to 84 in cycle 2 and cycle 3 becomes. 86. Improved student learning outcomes from the initial conditionsexhaustiveness cycle 1 to 47.36% to 64%, 86% cycle 2 and cycle3 to complete 100%.